Enzymatic β-Mannosylation of Phenylethanoid Alcohols - Lucia Černáková; Peter Haluz; Vladimír Mastihuba; Zuzana Košťálová; Elena Karnišová Potocká; Mária Mastihubová (Molecules)
Phenylethanoid glycosides (PhGs) are widely occurring secondary metabolites of medicinal plants with interesting biological activities such as antioxidant, anti-inflammatory, neuroprotective, antiviral, hepatoprotective, immunomodulatory, etc. They are characterized by a structural core formed by a phenethyl alcohol, usually tyrosol or hydroxytyrosol, attached to β-D-glucopyranose via a glycosidic bond. This core is usually further decorated by attached phenolic acids or another saccharide. Several studies suggest an important role of the saccharidic fragment in the biological activities of PhGs, provoking demand for new glycovariants of natural PhGs. This study presents the preparation of β-mannosylated analogs of tyrosol β-D-glucopyranoside (salidroside) and hydroxytyrosol β-D-glucopyranoside (hydroxysalidroside). While the chemical synthesis of β-D-mannopyranosides is rather challenging, they can be prepared by enzymatic catalysis. We found that Novozym 188, an industrial β-glucosidase, also contains β-mannosidase and used this enzyme in the preparation of tyrosol β-D-mannopyranoside and hydroxytyrosol β-D-mannopyranoside in 12 and 16% chemical yields, respectively, by transglycosylation from β-D-mannopyranosyl-(1→4)-D-mannose. The mannosylation was chemoselective and occurred exclusively on the primary hydroxyls of tyrosol and hydroxytyrosol, and the glycosylation of phenolic moieties of the aglycons was observed.